2019
DOI: 10.1080/15476286.2019.1572438
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses reveal groups of co-expressed, syntenic lncRNAs in four species of the genus Caenorhabditis

Abstract: Long non-coding RNAs (lncRNAs) are a heterogeneous class of genes that do not code for proteins. Since lncRNAs (or a fraction thereof) are expected to be functional, many efforts have been dedicated to catalog lncRNAs in numerous organisms, but our knowledge of lncRNAs in non vertebrate species remains very limited. Here, we annotated lncRNAs using transcriptomic data from the same larval stage of four Caenorhabditis species. The number of annotated lncRNAs in self-fertile nematodes was lower than in out-cross… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…Sequence similarity search and synteny conservation indicated that the lncRNAs of S. japonicum have synteny conservation with S. mansoni lncRNAs, even when there is a lack of sequence conservation. Pegueroles et al [28] analyses of lncRNAs sequence or synteny conservation between the Caenorhabditis spp. also identified a much higher number of lncRNAs with synteny conservation than with sequence conservation [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence similarity search and synteny conservation indicated that the lncRNAs of S. japonicum have synteny conservation with S. mansoni lncRNAs, even when there is a lack of sequence conservation. Pegueroles et al [28] analyses of lncRNAs sequence or synteny conservation between the Caenorhabditis spp. also identified a much higher number of lncRNAs with synteny conservation than with sequence conservation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Pegueroles et al [28] analyses of lncRNAs sequence or synteny conservation between the Caenorhabditis spp. also identified a much higher number of lncRNAs with synteny conservation than with sequence conservation [28].…”
Section: Discussionmentioning
confidence: 99%
“…Searches of lncRNAs conserved between amphioxus and vertebrates based on sequence similarity have been unsuccessful [14,15], probably due to the long evolutionary distance that separates these lineages [16]. Recently, however, a strategy to identify conserved intergenic lncRNAs (lincRNAs) by means of syntenic analyses has been successfully attempted, but limited to closely related species [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, syntenic lncRNAs have been reported in several organisms, including plants [68][69][70]. The conservation of genomic positions of lncRNAs and their target genes across related species has been investigated to consolidate their interactions [70].…”
Section: Functional Analysis Of Potential Novel Lncrnas Involved In Cmentioning
confidence: 99%